THE DAMPAK PARIWISATA TERHADAP KONDISI EKONOMI, SOSIAL-BUDAYA, DAN LINGKUNGAN MASYARAKAT DI DESA WISATA ADAT OSING KEMIREN BANYUWANGI: Bahasa Indonesia - Zakarias Seto Dwi Anggoro; Dewa Ayu Made Lily Dianasari; Hanugerah Kristiono Liestieandre (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2023)
Kemiren Osing Traditional Tourism Village, located in Banyuwangi City, has experienced significant growth in recent years. This development has impacted the local community, spanning economic, socio-cultural, and environmental dimensions. The primary objective of this study was to assess these impacts from the residents' perspective. A survey involving 141 household heads selected through a simple random sampling method was conducted. The data collected were analyzed using confirmatory factor analysis. It was found that tourism has had a substantial economic impact on the community, primarily by increasing business opportunities (X1.3), with a high loading factor score of 0.822. Furthermore, tourism has influenced the socio-cultural aspect by stimulating demand for arts and culture, as indicated by a loading factor score of 0.799 based on X2.1. Additionally, tourism has contributed to environmental awareness, with the highest loading factor score of 0.885, emphasizing the importance of cleanliness. This research underscores the importance of enhancing the quality of tourism activities to maximize benefits for the local community. It also highlights the need for stringent regulations to prevent conflicts related to economics, socio-culture, and the environment between investors and residents.